Efficacy of Kolofort in Combined Functional Gastroenterological Pathology: an Open Study - Yu. P. Uspenskiy; O. S. Mirzoev; Yu. A. Fominykh; A. A. Gnutov; S. V. Polyushkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The study aims to evaluate the efficacy and safety of Kolofort administration in patients suffering from irritable bowel syndrome (IBS) and functional dyspepsia (FD), as well as the prevalence of somatic and polymorbid psychomental disorders (distress, depression, anxiety and somatisation) in these patient groups using questionnaires “7×7” and “4DSQ”.Materials and methods. The study included 56 patients with IBS and FD diagnosed according to the Rome IV revision criteria and the Clinical Guidelines of the Russian Gastroenterological Association, the average age was 36.36 ± 6.42 years. All patients received Kolofort 2 times a day, 2 tablets per dose for 28 days.Results. The Kolofort therapy improved the clinical symptoms according to the “7x7” questionnaire; the primary mean total score was 17.7 ± 3.6, decreased to 10.3 ± 2.5 past 14 days (p < 0.0001) and to 7.6 ± 1.5 - past 28 days of therapy (p < 0.0001). On the 28th day of therapy, a 4DSQ survey revealed a 49.9% growth in patients with absent distress, a 29.3% decrease in moderate and 20.6% — in high distress cases (p < 0.0001). On the same term, the number of patients without depression increased by 21.4%, decreased by 17.9% with moderate depression and by 3.4% - with severe depression (p = 0.003); the number of patients without anxiety increased by 32.0%, decreased by 8.9% with moderate and by 23.1% — with severe anxiety (p < 0.0001); the number of patients with absent somatisation increased by 53.9%, decreased by 37.1% with moderate and by 18.6% — with severe somatisation (p < 0.0001).Conclusion. Patients with combined IBS and FD exhibit a high prevalence and severity of both somatic and polymorbid mental symptoms. The Kolofort therapy effectively suppresses clinical symptoms and reduces distress, depression, anxiety and somatisation.